The Responses of the Bakers, Longshoremen and Teamsters to Public Exposure - Taft, Philip (Quarterly Journal of Economics, 1960)
I. Introduction, 393. — II. The Teamsters' Union, 395. — III. The Longshoremen's Union, 397. — IV. The Bakers' Union, 400. — V. Obstacles to secession, 408. — VI. Doctrine of frustration of contract, 408. — VII. Contract bar doctrine, 409. — VIII. Conclusion, 410.